Effect of Intellectual Capital, Ownership Structure, And Operating Capacity on Financial Distress - Muhammad Rifki; Andy Setiawan (COMPETITIVE, 2025)
Financial distress remains a critical issue for companies, particularly in capital-intensive industries such as the energy sector.The purpose of this study is to determine the effect of intellectual capital, ownership structure, and operating capacity on financial distress. The population of this study includes energy companies listed on the Indonesia Stocks Exchange (IDX) for the period 2021-2023. Employing a purposive sampling method, 177 data observations were analyzed using panel data regression.. The results of this study indicate that (1) the intellectual capital variable has a positive effect on financial distress, suggesting that higher intellectual capital alone does not necessarily enhance financial stability (2) the institutional ownership variable has a negative effect on financial distress, indicating that strong institutional investor presence can improve financial resilience. (3) managerial ownership has no effect on financial distress, implying that managerial stakes may not directly impact financial health.and (4) operating capacity has a positive effect on financial distress, highlighting the potential risks associated with higher operational intensity. The modelâ€™s adjusted R2 value of 0,1367 indicates that 13,67%Â  of the variation in financial distress is explained by the tested variables. These results underscore the importance of effective corporate governance and financial management in mitigating financial distress. This study provides valuable insights for policymakers, investors, and corporate decision-makers in formulating strategies to enhance financial sustainability in the energy sector.